A temática gênero nas produções provenientes dos grupos de pesquisa da Universidade Federal do Pará - MAUÉS, Marilene Silva (Universidade Federal do Pará, 2011)
This paper aimed to carry out a mapping that would show the researchers scientific productions linked to groups of research in the Federal University of Pará (UFPA), it also aims to analyze how the gender theme gained evidence in researches carried out in the academic-scientific scenario of that institution, in the period of 1995-2006. Thus, the following questions had been raised: 1) What have they have been arguing about in the academic field, around the questions of gender? 2) How the scientific production generated in the data basis of research groups registered in the CNPq during the period of 1995-2006 is evidenced? 3) How the production generated by the researchers, in the research group is presented, taking into account the statistical figures in the UFPA campus in Belém? The data had been analyzed considering its quantity and quality by crossing the figures of scientific productivity - available in the site of the National Council of Scientific and Technological Development (http://www.cnpq.br) - with the theoretical references which delimitates the gender theme - Louro (2001) and Rosemberg (2001) -, aspects that allowed to make an x-ray of the production generated in the national scenario for posterior verticalization with the production research of the UFPA. Evidenced that great part of the research around the gender theme has approached allusive questions related to women and that those researches refute the explanations of biological basis in the composition of female and male, as well as they assume that culturally there is a relationship of power between opposite sexes. Moreover, the study showed that in the national panorama the genre found its place in the research group in the Human Sciences area; regarding to female participation in Science it was observed an androcentric parameter in the structure of scientific deeds, this aspect resounds in the quantitative process of academic productions of female authorship, considering that they still need to conciliate the professional career with the requirements of the private world; but, despite the male domain in the scientific productions, the studies on gender have been gaining praise in the research developed by women, not only in the national level but also in the local one. Regarding the figures of the UFPA, the gender have gained a place of prominence in the paraense production and these professionals have performed with care in that field showing a frequent production in a period of 11 years, even so they had to take on an incommensurable addition of work in consequence of the majority to be part of the teaching stuff of Post Graduation Programs in the UFPA. Thus, it is reassured that the research groups of the Institution mentioned here, even though with lesser quantitative expression in relation to the national scenario, they are of great relevance for the spread of the studies on this theme in the North region and for the projection of this university as an institutional place where the research produced guarantees national highlight.